Respostas
respondido por:
2
a)
3x + y = - 16 (3)
2x - 3y = - 17
9x + 3y = - 48
2x - 3y = - 17 (+)
-----------------------------
11x = - 65
x = - 65
------
11
3x + y = - 16
3 . ( - 65 ) + y = - 16
------
( 11 )
- 195 + y = - 16
-------
11
- 195 + 11y = - 176
-------------- -------
11 11
11y = - 176 + 195
11y = 19
y = 19
---
11
======================
b)
x + 3y = 5
2(x + y) + 4y = 5
2x + 2y + 4y = 5
2x + 6y = 5
x + 3y = 5 (-2)
2x + 6y = 5
- 2x - 6y = - 10
2x + 6y = 5 (+)
----------------------------
0 0 = - 5
R.: Sistema Impossível
3x + y = - 16 (3)
2x - 3y = - 17
9x + 3y = - 48
2x - 3y = - 17 (+)
-----------------------------
11x = - 65
x = - 65
------
11
3x + y = - 16
3 . ( - 65 ) + y = - 16
------
( 11 )
- 195 + y = - 16
-------
11
- 195 + 11y = - 176
-------------- -------
11 11
11y = - 176 + 195
11y = 19
y = 19
---
11
======================
b)
x + 3y = 5
2(x + y) + 4y = 5
2x + 2y + 4y = 5
2x + 6y = 5
x + 3y = 5 (-2)
2x + 6y = 5
- 2x - 6y = - 10
2x + 6y = 5 (+)
----------------------------
0 0 = - 5
R.: Sistema Impossível
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás